Estimating the cost of chronic kidney disease in Australia - Sean Randall; Crystal M. Y. Lee; Elizabeth Thomas; Aron Chakera; Kevin E. K. Chai; Richard Varhol; Kanika Mehta; Ashley Irish; Johan Conradie; Narelle Hadlow; Delia Hendrie; James H. Boyd; et al. (BMC Health Services Research)
Abstract Introduction Chronic kidney disease (CKD) is a significant burden on health systems globally, with limited up-to-date information on health system costs, particularly for non-dialysis patients. This study estimates the direct healthcare costs of CKD within Australia. Methods The study utilised the CKD.WA dataset, a linked repository for the state of Western Australia, containing public and private pathology, hospital, emergency and mortality data for over 2 million people, along with a secondary dataset of general practice records. Costs were calculated for individuals with CKD in 2019 and compared to controls without CKD to identify costs attributable to CKD. Cost items included hospital, emergency, medication, general practice, pathology, dialysis and outpatient services. Costs were expressed in 2023 AUD. Results There were 114,899 individuals with CKD in 2019. Average yearly costs attributable to CKD were $3,367 for Stage 1, $4,114 for Stage 2, $3,607 for Stage 3a, $6,572 for Stage 3b, $11,456 for Stage 4 and $62,558 for Stage 5. Non-dialysis hospital costs were the biggest contributor, followed by dialysis costs. The estimated total cost of CKD to Australia was $8.3 billion for 2019. Conclusion These findings highlight the significant cost burden of CKD. While CKD costs per individual are highest in later stages, the greater number of early-stage CKD cases means the majority of the cost burden is located among early-stage cases. Primary and secondary prevention strategies are likely key to reducing costs.